The Legitimacy of Indigenous Intellectual Property Rights’ claims (Strathmore Law Review, 2016)
The notions of indigenous peoples, indigenous knowledge, and heritage and culture have acquired wide usage in international debates on sustainable development and intellectual property protection since the turn of the 20th century. This paper, through an examination of the concept of intellectual property and its intersection with culture and heritage, elucidates the nature and scope of indigenous intellectual property rights as represented by traditional knowledge, traditional cultural expressions and genetic resources. This paper, through a review of the interface between indigenous knowledge systems and the intellectual property law regime, illustrates the limitations of conventional intellectual property rights systems i.e.: copyright, patent, trade secrets and trademark in providing adequate recognition and protection for indigenous intellectual property rights. It also posits that the establishment of a sui generis system of protection offers a plausible solution to the inadequacy of the existing regimes of protection. This paper ultimately seeks to illustrate indigenous people’s legitimate rights to control, access and utilize in any way, including restricting others’ access to, knowledge or information that derives from their unique cultural histories, expressions, practices and contexts, towards the creation of a better society.